The Great Restoration: Post-Communist Transformations from the Viewpoint of Comparative Historical Sociology of Restorations - Norkus, Zenonas (2023)
‘The revolutions of 1989’ remains the standard term used to describe the onset of post-commununist transformations more than thirty years ago. Zenonas Norkus proposes a completely new perspective, theorising them as the next wave of modern social restorations, starting with the post-Napoleonic restorations in 1815. A comparison of the 1789 French and 1917 Russian revolutions was seminal for the rise of comparative historical and sociological research on modern revolutions. The book extends and supplements the sociology of modern revolutions by the first systematic outline of the sociology of modern social restorations grounded in a comparison of post-Napoleonic and post-communist restorations